Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/ics.12574
|View full text |Cite
|
Sign up to set email alerts
|

The importance of 12R‐lipoxygenase and transglutaminase activities in the hydration‐dependent ex vivo maturation of corneocyte envelopes

Abstract: BackgroundTerminally differentiated keratinocytes acquire corneocyte protein envelopes (CPE) complexed with corneocyte lipid envelopes (CLE). These two structural components of the corneocyte envelopes (CEs) undergo maturation by gaining in hydrophobicity, rigidity and surface area. Linoleoyl acylceramides are processed by 12R‐lipoxygenase (12R‐LOX) and other enzymes before transglutaminase (TG) attaches ω‐hydroxyceramides to involucrin in the CPE. Concurrently, structural proteins are cross‐linked by TG that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Cornified cell envelopes undergo progressive maturation within the SC that results in increase of the cell stiffness ( Michel et al ., 1988 ; Milani et al ., 2018 ). This process appears to rely largely on hydration-dependent activities of transglutaminase 1 and 12R-lipoxygenase ( Guneri et al ., 2019 ). It is, therefore, not surprising that in AD, characterized by low NMF content and, consequently, reduced hydration, expression of mRNA and the corresponding proteins composing CE is decreased ( Trzeciak et al ., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cornified cell envelopes undergo progressive maturation within the SC that results in increase of the cell stiffness ( Michel et al ., 1988 ; Milani et al ., 2018 ). This process appears to rely largely on hydration-dependent activities of transglutaminase 1 and 12R-lipoxygenase ( Guneri et al ., 2019 ). It is, therefore, not surprising that in AD, characterized by low NMF content and, consequently, reduced hydration, expression of mRNA and the corresponding proteins composing CE is decreased ( Trzeciak et al ., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indirectly, filaggrin influences the SC mechanical integrity through its degradation products, which contribute to a pool of hygroscopic molecules collectively called natural moisturizing factors (NMF). NMF regulate SC hydration, crucial for the plasticity of the skin, its pH and activity of enzymes involved in key homeostatic processes in the SC including lipid synthesis, maturation of CE and desquamation ( Guneri et al ., 2019 ; Rawlings, 2014 ). Therefore, deficiency of filaggrin will likely affect mechanical stability of the SC and its resistance to cracking and chapping, common hallmarks of AD skin.…”
Section: Introductionmentioning
confidence: 99%
“…Omega-O-acylceramides, especially the linoleate-containing ones, are used in a complex enzymatic process to attach ceramides to the corneocyte protein envelope (CPE) [13][14][15][16][17][18]. Reduced levels of 12R-LOX and eLOX3 were reported in photodamaged cheek SC previously from Caucasian women and 12R-LOX in Chinese subjects [38][39][40]. In this study, we observed that the mass levels of 12R-LOX and eLOX3 were equivocal in all three ethnic groups indicating a lipoxygenase-relevant corneocyte maturation insufficiency in all ethnicities (Table 1A-C).…”
Section: Sc Proteomics Of Corneocyte Lipid Envelope Processing Enzymesmentioning
confidence: 99%
“…Compared to other body sites, facial skin shows elevated transepidermal water loss (TEWL, a measure of skin barrier function), and increased SC cohesion together with lower levels of SC ceramides and natural moisturising factors and higher serine, aspartic and matrix metalloprotease protease activity resulting in premature corneodesmosomal degradation and thinning of the SC [1,[20][21][22][23][24][25][26][27][28][29][30]. Relating to the immaturity of the cells, reduced loricrin levels together with lowered transglutaminase and 12Rlipoxygenase activities have been reported in photodamaged facial skin [31][32][33]. A summary of this biochemistry is described in Fig.…”
Section: Introductionmentioning
confidence: 99%